PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN SCRATCH UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA PELAJARAN IPAS KELAS IV UPT SPF SD NEGERI 101790 MARINDAL II - Sabrina, Sabrina; Destini, Rita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to produce scratch-based learning media in science lessons to be applied to learning in elementary schools and to determine the feasibility of scratch-based learning media in science lessons developed. The research method used in this study is the research and development (R&D) method with the ADDIE development model which consists of 5 stages, namely: analysis, design, development, implementation, evaluation. This study uses a validation sheet research instrument in the form of a questionnaire or questionnaire. The subject of this study is scratch-based learning media, the object of this study is learning materials that meet the needs and there are four expert studies or validators, namely media experts, material experts, teacher responses, and student responses in elementary schools. The results of this research are in the form of scratch-based learning media products to improve student learning outcomes in science lessons which are included in the